Pre-Service Teachers' Challenges in Classroom Management during Teaching Practice - Agustin Serliana; Praditya Putri Utami; Acep Bahrum Kamil (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Classroom management is one of the most important aspects of teaching, in this case was English, to create an effective and enjoyable learning environment. However, this is one of the challenges faced by pre-service teachers who have no experience previously. This study was conducted to find out what challenges are faced by pre-service English teachers related to classroom management. This research was conducted on four English Education students who were selected based on several criteria. Qualitative research design and interviews were used to collect data from the participants. The data that had been obtained from the interviews were transcribed, coded according to the results of their answers and translated into English. Based on the results of the study, there are three problems that are often faced by student-teachers related to students' bad attitudes and their learning motivation, including disrespecting the teacher, sleep during the class and lack of participation.